2020
DOI: 10.1155/2020/4639382
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Analytical Heat Source Model for Numerical Simulation of Temperature Field in Friction Stir Welding

Abstract: In the conventional analytical model used for heat generation in friction stir welding (FSW), the heat generated at the pin/ workpiece interface is assumed to distribute uniformly in the pin volume, and the heat flux is applied as volume heat. Besides, the tilt angle of the tool is assumed to be zero for simplicity. ese assumptions bring about simulating deviation to some extent. To better understand the physical nature of heat generation, a modified analytical model, in which the nonuniform volumetric heat fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…At present, most numerical simulation of laser cladding adopts Gaussian heat source model, and planar Gaussian heat source model is a typical planar heat source distribution function [10]. This model is to apply heat in a circle with a given radius according to the distribution of heat source energy in a plane according to the Gaussian function.…”
Section: Heat Source Modelmentioning
confidence: 99%
“…At present, most numerical simulation of laser cladding adopts Gaussian heat source model, and planar Gaussian heat source model is a typical planar heat source distribution function [10]. This model is to apply heat in a circle with a given radius according to the distribution of heat source energy in a plane according to the Gaussian function.…”
Section: Heat Source Modelmentioning
confidence: 99%
“…It has been shown that the tool shoulder plays a major role in the generation of FSW heat [16]. Accordingly, the welding temperature normally decreases towards the weld root [7,8,[16][17][18][19][20][21][22][23]. In contrast, the temperature distribution in the width direction of the stir zone is often found to be nearly symmetric [8,11,19,[24][25][26][27].…”
Section: Weld Thermal Cyclementioning
confidence: 99%
“…Gadakh [11], Yaduwanshi [12], Ghetiya [13], Liu W M [14], Bonifaz [15], Liu X Q [16] based on Schmidt's heat source model, separately studied the effects of rotational speed and welding speed, axial pressure, cone angle of the tool pin, backing plate type and welding inclination angle on the temperature distribution of thin plates. Among them, Ghetiya's research showed that the tensile strength and microhardness of joints are affected by temperature.…”
Section: Introductionmentioning
confidence: 99%